Low back pain in pregnancy - TASHIRO, Toshiyuki (The Journal of Japanese Society of Lumber Spine Disorders, 1996)
Low back pain is quite common during pregnancy. For analysis of the incidence, the clinical presentation, and the risk factor of low back pain in pregnancy, 175 women were interviewed and examined within 10 days after giving birth. It was found that+68% of these patients suffered from low back pack pain during pregnancy, and that with 77.3% of them, the pain started by the 31 th week of pregnancy.The difference was not significant statistically between the patients with low back pain and those without it in the age, the history of previous pregnancy, the history of previous back pain, weight gained by the mother during pregnancy, degree of obesity of the mothe before pregnancy, and the baby's birth weight. In the first pregnancy, however, young mothers (under 30 years of age) showed a higher risk of back pain. By postdelivery examination 18% of the patients had the tenderness of the sacroiliac area. Follow-up examinations showed, however, that the pain improved within one month with 80% of these patients.